PERHITUNGAN KAPASITAS DUKUNG AKSIAL FONDASI TIANG APARTEMEN GRAND DHIKA CITY BEKASI - , ULFA KHOIRUNITA G ([Yogyakarta] : Universitas Gadjah Mada, 2014)
On the construction of Cempaka Apartment Grand Dhika City Bekasi project, bottom structure using concrete slab foundations. With the aim of applying the material that never learned to calculate the original data used in the planning of the foundation piles. As well as to deepen the knowledge about the bearing capacity of piles. In preparing the final report, the method used is the method of observation, interview methods, Studies Library and Documentation. The manual calculation using the theories foundation techniques to calculate the axial bearing capacity of piles. The data used is the data obtained from the planner. Once the calculation is done manually by the formula, the bearing capacity of piles safe for use as foundation piles with pile capacity Spun Pile Ã600mm worth 2392.21 kN and for Bored Pile pole Ã1000mm worth 6605.75 kN. With capacity on Pile Cap group type P2, P3, P8, P14 and P37 respectively have a value 7616.797 kN, 12468.63 kN, 52582.01 kN, 52991,567 kN, 159846.66 kN.